2006
DOI: 10.1111/j.1365-2826.2006.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Sleep Deprivation and Sleep Recovery: Effects on the Hypothalamic–Pituitary–Adrenal Axis Activity, Energy Balance and Body Composition of Rats

Abstract: Numerous studies indicate that sleep deprivation alters energy expenditure. However, this conclusion is drawn from indirect measurements. In the present study, we investigated alterations of energy expenditure, body composition, blood glucose levels, plasma insulin, adrenocorticotropic hormone (ACTH) and corticosterone levels immediately after 4 days of sleep deprivation or after 4 days of sleep recovery. Rats were sleep deprived or maintained in a control environment (groups sleep-deprived/deprivation and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
93
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 52 publications
(79 reference statements)
16
93
1
3
Order By: Relevance
“…Both epidemiological and clinical data suggest that disturbed sleep may contribute to the development of various diseases, e.g., obesity and type 2 diabetes (4,6,7,12,36,37). Restricted sleep also leads to alterations in food intake and its regulatory hormones, particularly an increased appetite and preference for fat, together with increased levels of ghrelin and decreased levels of leptin (38, 39).There are several rodent models for sleep deprivation; for example, the disk-over-water method (8, 28), the inverted flowerpot (or platform) paradigm (13,24), and the slowly rotating drum paradigm (1,26,30). In general, the changes in blood hormone levels and food intake in these models are similar to the findings in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both epidemiological and clinical data suggest that disturbed sleep may contribute to the development of various diseases, e.g., obesity and type 2 diabetes (4,6,7,12,36,37). Restricted sleep also leads to alterations in food intake and its regulatory hormones, particularly an increased appetite and preference for fat, together with increased levels of ghrelin and decreased levels of leptin (38, 39).There are several rodent models for sleep deprivation; for example, the disk-over-water method (8, 28), the inverted flowerpot (or platform) paradigm (13,24), and the slowly rotating drum paradigm (1,26,30). In general, the changes in blood hormone levels and food intake in these models are similar to the findings in humans.…”
mentioning
confidence: 99%
“…Sleep deprivation decreased plasma insulin (13) and leptin levels (8), and increased food intake was observed in some (8,13,16,17,28,29) but not all studies (1). However, the most consistent finding among these studies is that sleep-deprived rats lose weight (1,8,13,16,17,28,29), which is in contrast to the human finding where a lack of sleep generally is associated with weight gain (6, 14).The reason for this difference between rats and humans is unknown. There is some indirect evidence that the differences in weight gain vs. weight loss might be related to the nature of the sleep restriction protocol.…”
mentioning
confidence: 99%
“…Previous studies had shown that sleep disturbances are frequently associated with stress exposure [1,3,18,24,28,32] and that SD is an effective stressor. Intracerebroventricular injection of CRF into rats induces arousal [46] and consequently reduces NREM sleep concomitant with a significant decrease in spectral power in lower frequencies (1-6 Hz) and increases in high frequencies (32-64 Hz) [8].…”
Section: Discussionmentioning
confidence: 99%
“…33 When this method is used to deprive rats of REM sleep for four days, it leads to a decrease in plasma insulin levels, which is secondary to a significant reduction in body weight. 34 Another commonly used method in animal sleep restriction research is the disk over water method, extensively described by Rechtschaffen and colleagues. 35,36 In short, the experimental animal is housed on a horizontal disk above water.…”
Section: Human Studies On Sleep and Glucose Homeostasismentioning
confidence: 99%